Analisa Efektivitas Organisasi Balai Pelaksana Pemilihan Jasa Konstruksi (BP2JK) Wilayah Sulawesi Barat - Iwan; Sudarman Supardi; Watono (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2025)
BP2JK currently has an organizational structure with duties and authorities that have been determined for each section. However, in its implementation there are still some unclear instructions from leaders in carrying out tasks, and there are still leaders who do not pay attention to the needs and desires of subordinates. The effectiveness of an organization can be influenced by work engagement, transformational leadership, organizational culture, and knowledge management. Therefore, improvements through human resources are very necessary in restoring the performance of a company or organization. Objective: The aim of this research is to identify factors and analyze the level of significance of factors that influence the effectiveness of the BP2JK organization in the West Sulawesi Region. Method: The research method used is quantitative research. The unit of analysis used in this research focuses on individual employees of BP2JK West Sulawesi Region with a population of 100 people. The sampling technique to determine the sample that will be used in this research uses a non-probability sampling technique, namely purposive sampling with a sample result of 80 people. The instrument used in this research was a questionnaire. Results: The results obtained in this research are the influence of transformational leadership on organizational effectiveness resulting in a t-statistic of 2,632 > 1.98. Can be concluded Acceptable. The influence of organizational culture on organizational effectiveness produces a t-statistic of 1.257 < 1.98. Can be concluded Unacceptable. The influence of knowledge management on organizational effectiveness produces a t-statistic of 0.818 < 1.98. Can be concluded Unacceptable. The influence of work engagement on organizational effectiveness produces a t-statistic of 4,775 > 1.98. Can be concluded Acceptable. Conclusion: Transformational leadership factors and work engagement have a significant effect on organizational effectiveness. The factors of organizational culture and knowledge management do not have a significant effect on organizational effectiveness. It is hoped that the results of this research can provide input to the BP2JK West Sulawesi Region in an effort to increase organizational effectiveness.